From bench to bedside: combining HDAC inhibitors with standard therapies in rhabdomyosarcoma treatment - Macrì, Elisa; Attili, Marika; Locatelli, Franco; Marampon, Francesco; Pomella, Silvia (Frontiers in Cell and Developmental Biology, 2026)
Rhabdomyosarcoma (RMS) is the most prevalent soft tissue sarcoma in children, and despite advances in multimodal therapy, progress in improving the survival of high-risk patients has been limited. Increasing evidence indicates that epigenetic dysregulation contributes to RMS pathogenesis and therapeutic resistance, particularly through aberrant activity of histone deacetylases (HDACs). HDAC inhibitors (HDACi) have shown promise in preclinical RMS models, showing enhancing of the efficacy of standard chemotherapies and radiotherapy. This mini-review summarizes recent studies exploring HDAC inhibition in combination with first-line therapies, examines the mechanistic basis for therapeutic synergy, and discusses opportunities and challenges in translating HDACi-based combinations to the clinic. By integrating mechanistic insights with translational evidence, this review outlines current progress and proposes future directions for development of HDACi-enhanced treatment strategies for this aggressive pediatric malignancy.